Development of The "Kisah Si Jojo" Android Application Based on Augmented Reality with Unity 3D - Pinasti Dwi Utami; Cindy Rachmawati; Erliana Dewi Saputri; Ery Nur Widiyanto; Arum Sartika; Ulfa Ardianawati (Journal of Software Engineering, Information and Communication Technology (SEICT), 2022)
Oriented towards the PISA analysis report, the results of the literacy and numeracy abilities of Indonesian students are low and very concerning. Apart from that, there are other problems regarding the ability and interest in reading of Indonesian students which are still below average. The purpose of this research is to motivate and increase students' interest in reading. Therefore, we need a learning media that can encourage students' interest and reading skills with the help of technology, namely through the development and creation of an android literacy application "Kisah Si Jojo" based on Augmented Reality Unity 3D. This android literacy application "Kisah Si Jojo" talks about the importance of tolerance between friends. The research model used in this study is ADDIE with six stages including starting from analysis, design, development, implementation, and evaluation. Based on the research results it is known that the android literacy application "Kisah Si Jojo" is developing well and can be used according to its function.